2020
DOI: 10.1111/ecc.13237
|View full text |Cite
|
Sign up to set email alerts
|

How psychosocial interventions meet the needs of children of parents with cancer: A review and critical evaluation

Abstract: A parent's cancer affects the whole family (Faulkner & Davey, 2002). Parents diagnosed with cancer and their spouses have limited capacity due to the demands of the illness (Gazendam-Donofrio et al., 2008; Helseth & Ulfsaet, 2005), with many reporting feelings of guilt about failing to be a "good parent" and struggles in communicating with their children about the cancer (Semple & McCance, 2010; Zahlis & Lewis, 2010). The treatment course may take months or even years, throughout which children must contend wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 68 publications
1
15
0
2
Order By: Relevance
“…The results of the Wonders & Worries intervention reported here contribute to the limited body of evidence regarding community based interventions designed specifically for children who have a parent with cancer. Recent, systematic reviews have concluded that most “existing studies do not meet the methodological rigor to make conclusions about intervention effectiveness, with studies that lack standardization, randomization and sufficient study control” 32 . To our knowledge, this is the first randomized clinical trial study of a manualized child‐centered intervention for families who have a parent diagnosed with cancer 15 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of the Wonders & Worries intervention reported here contribute to the limited body of evidence regarding community based interventions designed specifically for children who have a parent with cancer. Recent, systematic reviews have concluded that most “existing studies do not meet the methodological rigor to make conclusions about intervention effectiveness, with studies that lack standardization, randomization and sufficient study control” 32 . To our knowledge, this is the first randomized clinical trial study of a manualized child‐centered intervention for families who have a parent diagnosed with cancer 15 .…”
Section: Discussionmentioning
confidence: 98%
“…Recent, systematic reviews have concluded that most "existing studies do not meet the methodological rigor to make conclusions about intervention effectiveness, with studies that lack standardization, randomization and sufficient study control". 32 To our knowledge, this is the first randomized clinical trial study of a manualized child-centered intervention for families who have a parent diagnosed with cancer. 15 The W&W intervention significantly improved parenting concerns, parenting selfefficacy, and family emotional well-being; effect sizes range from moderate to large: 0.59 to 1.0.…”
Section: Discussionmentioning
confidence: 99%
“…For this overview, the PubMed, Google Scholar, and Connected Papers databases were searched using the keywords ‘intervention’, ‘parental’, ‘parenting’, ‘support’, and ‘cancer’. Four literature reviews describing interventions created for family members facing parental cancer were identified [15,23 ▪ ,24,25 ▪ ]. Given the scarcity of recent publications in this area, we expanded our search to articles published in the last 10 years.…”
Section: Overview Of Parenting Interventions For Parents With Cancer ...mentioning
confidence: 99%
“…Sie adressieren aber häufig nur einen Teil der Familienmitglieder und/oder einen Teil der oben aufgezeigten Unterstützungsbedarfe [10]. Beim Abgleich von 15 vorhandenen Interventionen mit den oben definierten Bedarfen [5] wurde keine Intervention identifiziert, die alle angesprochenen Bedürfnisse adressierte [20].…”
Section: Vorhandene Interventionen Heterogenunclassified